Eliminating race-based mental health disparities : promoting equity and culturally responsive care across settings - Williams, Monnica T.; Rosen, Daniel C.; Kanter, Jonathan; Arredondo, Patricia (Context Press, an imprint of New Harbinger Publications, Inc., 2019)
In this edited volume, three leading experts in race, mental health, and contextual behavior science address the urgent problem of racial inequities and biases, which often prevent people of color from seeking mental health services--leading to poor outcomes if and when they do receive treatment. This critical and timely guide provides clinicians and educators with evidence-based recommendations for addressing inequities at multiple levels, as well as best practices for compassionately and effectively helping clients across a range of cultural groups and settings.